SELF-EFFICACY OF THE FOURTH SEMESTER STUDENTS OF ENGLISH DEPARTMENT OF UKI TORAJA IN - Yuli Kondopare (Publikasi dan UKI Press UKI Toraja., 2022)
The objective of this research is to find out the level of self-efficacy in speaking by the fourth semester students of the English Department at UKI Toraja. This research applied quantitative and qualitative methods. The subjects of this research were the students of the English Department of UKI Toraja. The data was collected by applying distribution questionnaires and voice recording. The obtained data qualitative data was analyzed in four major phases; data collection, data reduction, data display and conclusion. The result of the research showed that the fourth semester students of the English Department have high and moderate self-Efficacy. Based on the data From the questionnaire students have high self-efficacy and the data from the interview students have high and moderate self-efficacy.